The Effect of The CAMEL Method on Profitability in General Banking Listed on The Indonesian Stock Exchanges in 2020-2022 - Rayhan, Ainun Putri; Permatasari, Dinda; Cahyani, Ikah Afri; Azizah, Yasmin Fatihatul; Putra, Haidar Tri; Mudjiyanti, Rina (Kompartemen : Jurnal Ilmiah Akuntansi, 2024)
This research aims to determine the effect of health level using the CAMEL method on profitability. The variables in this research are capital, assets, management, earnings, liquidity, and profitability. These variables are measured by CAR, NPL, NIM, BOPO, LDR, and ROA. This research uses secondary data obtained from the Q2 and Q4 financial reports of banks listed on the IDX for 2020-2022 which were accessed from the websites www.idx.co.id. The population in this study were commercial banks listed on the IDX for the 2020-2022 period. The statistical analysis technique used is Multiple Linear Regression analysis. These results show that CAR and LDR have no effect on ROA. NIM has a positive effect on ROA, while NPL and BOPO have a negative effect. Every year there is bad credit so the NPL is uncertain. NIM affects ROA, so that interest income on productive assets managed by the bank increases so that the possibility of the bank being in trouble becomes smaller and the level of profitability can grow.